The dynamic welfare habitus and its impact on Brazilian migration to Lisbon and Barcelona - Jolivet, Dominique (2021)
Little is known on how people’s way of thinking and doing around welfare provision – what we call the welfare habitus – plays a role in migration and how such cultural references change over the migration process. Through an empirical case study on Brazilian migration to Southern Europe, this article explores the dynamism of the welfare habitus focusing on three elements. First, the welfare-related resource environment in the countries of origin and destination. Second, the role of the welfare habitus in shaping migration aspirations. Third, the transformative learning process taking place during the life course and the migration experience. The article draws on a literature review, the analysis of secondary quantitative data and 24 in-depth semi-structured qualitative interviews collected in 2016 in Lisbon and Barcelona among men and women born in Brazil selected at different stages of the life course –young people without children, parents of school-aged children and people aged 55 or more. Drawing on practice theory the paper looks at the interaction between external structures, habitus and everyday actions around welfare provision in contexts of migration. Doing so, the paper contributes to a better understanding of the effect of welfare provisions in the country of origin on migration focusing on the temporal perspective.